TREND AND TRADEOFF BETWEEN ACCRUAL EARNINGS MANAGEMENT AND REAL EARNINGS MANAGEMENT IN INDONESIA - Widyaningsih Azizah (Media Riset Akuntansi, Auditing & Informasi, 2017)
This research was carried out to test trend of earnings management in Indonesia. By understanding the trend of earnings management, it can be found out what scheme of earnings management practice in Indonesia. The sample used were 31 (thirty one) non financial, hotel, travel, transportation and real estate companies that listed in Indonesia Stocks Exchange from 1991 to 2014. The time of observation was from 1993 to 2013. Research model was using multiple regression method. The result showed there was no trend increasing of accrual earnings management during research period. Practice of accrual earnings management in Indonesia that tends fluctuate shows there is a tradeoff or substitution of earnings management technique from accrual to real earnings management.